Teduglutide in pediatric intestinal failure: A position statement of the Italian society of pediatric gastroenterology, hepatology and nutrition (SIGENP). Issue 10 (October 2022) - Diamanti, A.; Lezo, A.; D'Antiga, L.; Gandullia, P.; Spagnuolo, M.I.; Roggero, P.; Capriati, T.; Lionetti, P.
Abstract: In recent years, the spectrum of possible treatments for Intestinal Failure (IF)-Short Bowel Syndrome (SBS) has been enriched by the implementation of GLP-2 analogues. In Italy, teduglutide (Ted), an analogue of GLP-2, was approved in January 2021 by the Italian Regulatory Agency for Drugs (AIFA) for IF-SBS patients ≥1 year old. According to the Agency indications, Ted can now be prescribed by regional reference centers, with costs fully charged to the National Health Service. Following pediatric-use approval in our country and in light of scarce evidence in childhood, the pediatric network for IF of the Italian Society for Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP) planned to share management methods of Ted in pediatric IF. The main purpose was to identify the best candidates from a cost-effective perspective. Thus, focusing on available literature and on expert opinions, the present position statement provides consensus-based recommendations on the use of Ted for pediatric gastroenterologists and nutritionists treating children with SBS.